The mitochondrial genome of Carex pseudochinensis H. Lév. & Vaniot, an endemic sedge in Korea - Jieun Lee; Sang Chul Choi; Sangtae Kim (Mitochondrial DNA. Part B. Resources)
Carex pseudochinensis H. Lév. & Vaniot is an endemic species in Korea and is included in the clade of section Paludosae in the recent classification system. We present the complete mitochondrial genome sequence of C. pseudochinensis based on the POLAP pipeline with both long- and short-read sequences. The mitochondrial genome is 997,628 bp in length, containing two large regions of 536.94 and 419.04 kbp, respectively, and a pair of direct repeat regions of about 20.25 kbp. The genome contains 57 genes, including 31 protein-coding genes, 20 tRNAs, and 6 rRNAs. Phylogenetic analysis based on mitochondrial proteomes, including those from ten species of related taxa, confirmed a close phylogenetic relationship between C. breviculmis and C. pseudochinensis.